Integrated analysis of miRNA and mRNA expression profiles in the brains of BTBR mice. Issue 3 (9th March 2020) - Wang, Min; He, Jing; Zhou, Yun; Lv, Na; Zhao, Min; Wei, Hongen; Li, Rongshan
Abstract: The BTBR T +  Itpr3 tf (BTBR) mouse has developmental disorders in brain and many aberrant neuroanatomical structures and brain dysfunction. However, identification of the pathological mechanisms underlying abnormal brain development in the brains of BTBR mice is still lacking. Increasingly evidence showed that epigenetics plays an important role in the processes of brain development. In this study, we analyzed microRNA (miRNA) and mRNA expression profiles in the cortical brain tissue from BTBR mice, using RNA sequencing. As compared to C57BL/6J (B6) mice, 1, 271 differentially expressed genes (DEGs) and 36 known differentially expressed miRNAs (DEMs) were found in the brain from BTBR mice. The functional annotation and categories of DEGs and DEMs were analyzed. Integration analysis identified 103 known miRNA–mRNA interaction pairs. We further verified selected several genes and miRNAs which may be associated with brain development using quantitative RT‐PCR (qRT‐PCR). Finally, we speculate that reduced myelin‐associated oligodendrocytic basic protein and transmembrane proteins 260 may be linked with abnormal brain development in BTBR mice. Abstract : The BTBR T +   Itpr3 tf (BTBR) mouse has developmental disorders in brain and many aberrant neuroanatomical structures and brain dysfunction. In this study, we analyzed microRNA (miRNA) and mRNA expression profiles in the cortical brain tissue from BTBR mice, using RNA sequencing. As compared to C57BL/6J (B6) mice, 1, 271 differentially expressed genes (DEGs) and 36 known differentially expressed miRNAs (DEMs) were found in the brain from BTBR mice.